Characteristic features of the style of the works of the Egyptian writer J. Hak - Көптілеуова, Д.; Жумажанова, Ф. (Journal of Oriental Studies, 2017)
Bed scenes in his work J. Hakki uses exclusively for artistic purposes, with a certain meaning, and not to interest the reader, or make his stories entertaining. The reader sees exactly how much is necessary to understand the feelings and experiences of the characters. The means which used by the author reflect the reality in his works.